Respiratory Muscle Function Tests and Diaphragm Ultrasound Predict Nocturnal Hypoventilation in Slowly Progressive Myopathies - Spiesshoefer, Jens; Lutter, Riccarda; Kabitz, Hans-Joachim; Henke, Carolin; Herkenrath, Simon; Randerath, Winfried; Young, Peter; Dreher, Michael; Görlich, Dennis; Boentert, Matthias (Frontiers in Neurology, 2021)
Introduction: In slowly progressive myopathies diaphragm weakness early manifests through sleep-related hypoventilation as reflected by nocturnal hypercapnia. This study investigated whether daytime tests of respiratory muscle function and diaphragm ultrasound predict hypercapnia during sleep. Methods: Twenty-seven patients with genetic myopathies (myotonic dystrophy type 1 and 2, late-onset Pompe disease, facioscapulohumeral dystrophy; 48±11 years) underwent overnight transcutaneous capnometry, spirometry, measurement of mouth occlusion pressures, and diaphragm ultrasound. Results: Sixteen out of 27 patients showed nocturnal hypercapnia (peak ptcCO2 ≥50 mmHg for ≥30 minutes or increase of ptcCO2 by 10 mmHg or more from the baseline value). In these patients, forced vital capacity (FVC; % predicted) and maximum inspiratory pressure (MIP; % of lower limit or normal or LLN) were significantly reduced compared to normocapnic individuals. Nocturnal hypercapnia was predicted by reduction of FVC <60% (sensitivity 1.0, area under the curve/AUC 0.82) and MIP (%LLN) <120% (sensitivity 0.83, AUC 0.84), the latter reflecting that in patients with neuromuscular disease pre-test likelihood of abnormality is per se higher than in healthy subjects. Diaphragm excursion velocity during a sniff maneuver excluded nocturnal hypercapnia with high sensitivity (0.90) using a cut-off of 8.0 cm/sec. Conclusion: In slowly progressive myopathies, nocturnal hypercapnia is predicted by FVC <60% or MIP <120% (LLN). As a novelty, nocturnal hypercapnia can be excluded with acceptable sensitivity by diaphragm excursion velocity >8.0 cm/sec on diaphragm ultrasound.